Essential Oils: An Effective Therapeutic Strategy against SARS-CoV-2 - Palai, Santwana; Kesh, Shyam Sundar (International Journal of Bio-resource and Stress Management, 2021)
Thousands of individuals have perished as a result of Covid-19 and it has turned into a global problem. The novel coronavirus 2019 (nCoV-2019), also known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has spread rapidly following its discovery in Wuhan patients with acute pneumonia in China. No medication or vaccine are available to treat human coronavirus infection successfully. The alternative therapies and cures are not are effective or authorised to treat Corona virus. Treatments are primarily supportive because no particular pandemic cure has been licenced. New interventions will most likely take months to years to mature. Using antiviral medicinal herbs as an auxiliary or supportive therapy seems to be a viable alternative. The essential oils of medicinal plants have antiviral and immunomodulatory effects. Being rich in antioxidants, essential oils can be used to develop new antiviral remedies. Such beneficial essential oils are being evaluated and exploited for its potent therapeutic use against many viruses. These natural compounds bestow antiviral actions by disrupting the viral life cycle during viral entry, assembly, replication, discharge and virus-specific host targets. This study highlights the essential oils derived from medicinal and aromatic plants with in vitro and in vivo antiviral effects. Essential oils having known pharmacokinetic and pharmacodynamic properties can be repurposed as a strategy against deadly SARS-CoV-2 infection. These essential oils of herbal plants can be an effective therapeutic strategy against SARS-CoV-2 when used along with conventional antiviral medicines.